BS ENISO/IEC 21122-2 AMD 1. Information technology. JPEG XS low-latency lightweight image coding system. Part 2. Profiles and buffer models. Profile and sublevel for 4:2:0 content (26th April 2022) - British Standards Institution,
No abstract available